Income Smoothing: The Role Cash Holding, Bonus Plan, and Winner/Loser Stock - Firmansyah, Wahyuda Dian; Mulyaningtyas , Mulyaningtyas (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
The purpose of this study is to see if cash holding, bonus plans, and winner/loser stock have an effect on income smoothing in Indonesian Stock Exchange-listed food and beverage sub-sector companies. The population for this study was 34 food and beverage sub-sector enterprises selected using a purposive sampling method, yielding a total sample of 19 companies during a two-year period, 2020-2021. The research data is quantitative, including secondary data sources obtained through intermediaries. This study employed multiple linear regression using the SPSS 26 program. The results revealed that cash holding, bonus plan, and winner/loser stock had little influence on income smoothing.